Systematic identification and functional characterization of the CFEM proteins in poplar fungus Marssonina brunnea - Qian, Yulin; Zheng, Xinyue; Wang, Xueying; Yang, Jun; Zheng, Xiangyang; Zeng, Qirui; Li, Jinwen; Zhuge, Qiang; Xiong, Qin (Frontiers in Cellular and Infection Microbiology, 2022)
Proteins containing Common in Fungal Extracellular Membrane (CFEM) domains uniquely exist in fungi and play significant roles in their whole life history. In this study, a total of 11 MbCFEM proteins were identified from Marssonina brunnea f. sp. multigermtubi (MULT), a hemibiotrophic pathogenic fungus on poplars that causes severe leaf diseases. Phylogenic analysis showed that the 11 proteins (MbCFEM1-11) were divided into three clades based on the trans-membrane domain and the CFEM domain. Sequence alignment and WebLogo analysis of CFEM domains verified the amino acids conservatism therein. All of them possess eight cysteines except MbCFEM4 and MbCFEM11, which lack two cysteines each. Six MbCFEM proteins with a signal peptide and without trans-membrane domain were considered as candidate effectors for further functional analysis. Three-dimensional (3D) models of their CFEM domains presented a helical-basket structure homologous to the crucial virulence factor Csa2 of Candida albicans. Afterward, four (MbCFEM1, 6, 8, and 9) out of six candidate effectors were successfully cloned and a yeast signal sequence trap (YSST) assay confirmed their secretion activity. Pathogen challenge assays demonstrated that the transient expression of four candidate MbCFEM effectors in Nicotiana benthamiana promoted Fusarium proliferatum infection, respectively. In an N. benthamiana heterogeneous expression system, MbCFEM1, MbCFEM6, and MbCFEM9 appeared to suppress both BAX/INF1-triggered PCD, whereas MbCFEM8 could only defeat BAX-triggered PCD. Additionally, subcellular localization analysis indicated that the four candidate MbCFEM effectors accumulate in the cell membrane, nucleus, chloroplast, and cytosolic bodies. These results demonstrate that MbCFEM1, MbCFEM6, MbCFEM8, and MbCFEM9 are effectors of M. brunnea and provide valuable targets for further dissection of the molecular mechanisms underlying the poplar-M. brunnea interaction.